Effects of a culturally specific tobacco cessation intervention among African American Quitline enrollees: a randomized controlled trial - Monica Webb Hooper; Kelly Carpenter; Michael Payne; Ken Resnicow (BMC, 2018)
Abstract Background African Americans suffer disproportionately from tobacco-related illness and have more difficulty quitting smoking than other racial/ethnic groups. Previous research indicates that African American treatment-seekers are high utilizers of tobacco quitlines, yet cessation rates via quitlines are lower relative to whites. The goal of the present study is to test the effectiveness of adding a culturally specific, video-based, adjunct to standard quitline care. It is hypothesized that the integration of an evidence-based intervention (Pathways to Freedom: Leading the Way to a Smoke-Free Community©; PTF) into quitline services will increase cessation and treatment engagement compared to control conditions, and that effects will be moderated by sociocultural factors (e.g., culturally specific intervention expectancies, acculturation, and ethnic identity). Methods This study is a 3-arm semi-pragmatic randomized controlled trial (RCT). Participants will be 1050 enrollees in the North Carolina State quitline (QuitlineNC) who self-identify as African American. Usual quitline care includes up to 4 proactive quit coaching calls, website access, and two-weeks of nicotine patch therapy. Eligible study participants will be randomized to receive (1) standard quitline services plus PTF (PTF); (2) quitline services plus a standard tobacco cessation DVD (attention control); or (3) quitline services alone (usual care). Assessments will be conducted at baseline, 3 and 6-months post-enrollment. The primary outcome will be biochemically verified 7 day ppa at 6-months. Generalized linear mixed models (GLMMs) and hierarchical logistic regression will be used to assess the effects of treatment group on cessation outcomes and to test potential moderators. Discussion This study will answer questions regarding the implementation and effectiveness of integrating a culturally specific video intervention into a real-world, population-level tobacco intervention. It will also aid our understanding of individual-difference variables that are associated with success. If an incremental benefit is found, this trial will have implications for increasing the responsiveness of tobacco quitlines for African Americans, reducing tobacco cessation disparities, and best practices for improving minority health. In addition, the PTF intervention has the potential for widespread disseminated through quitlines, which are available across the United States. Trial registration Clinicaltrials.gov NCT03064971 . Registered on February 22, 2017.